From Passive to Interactive: How Teams Games Tournament Transforms Science Education for Fifth Graders - Kadek Arya; Herlina Herlina; Asriani Asriani; Zulnuraini Zulnuraini; Putriwanti Putriwanti (Papanda Publisher, 2026)
Low science (IPAS) outcomes in Indonesian elementary schools stem from teacher-centered methods, limiting student engagement and conceptual understanding, as evidenced by national assessments (54.3% competency rate) and PISA scores (383 vs. OECD 485). This study examines the pure Teams Games Tournament (TGT) cooperative model's effect on fifth-grade cognitive learning in light properties material under the Independent Curriculum. Employing a quantitative pre-experimental one-group pretest-posttest design, the study sampled 29 fifth-grade students at SD Inpres 1 Talise via purposive sampling. Instruments included a 20-item multiple-choice test (14 valid, Cronbach's Alpha 0.875), observation sheets, and interviews. TGT was implemented over three meetings, with data analyzed using Shapiro-Wilk normality, Paired Sample T-Test, and N-Gain via SPSS 27. Pretest mean was 40.64, rising to 67.48 posttest (p < 0.001, t = -9.01), with moderate N-Gain (0.4413). Implementation fidelity improved from 86% to 97%, though two students showed minimal gains due to group adaptation issues. Findings support Vygotsky's constructivism, aligning with prior TGT studies (e.g., Listiani et al., 2025), but highlight needs for media integration. Implications include low-cost active learning strategies; limitations involve small sample and no control group. Future research should use quasi-experiments for broader generalizability.